2014
DOI: 10.1111/scd.12097
|View full text |Cite
|
Sign up to set email alerts
|

Association of salivary triglycerides and cholesterol with dental caries in children with type 1 diabetes mellitus

Abstract: Both salivary cholesterol and triglycerides levels were significantly higher in children with type 1 diabetes mellitus. Salivary triglycerides showed a significant association with dental caries in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Eleven studies reported a DMFT/DMFS index significantly higher among type 1 diabetics, four found a significantly lower index and 20 did not find statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Eleven studies reported a DMFT/DMFS index significantly higher among type 1 diabetics, four found a significantly lower index and 20 did not find statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 87%
“…Forty‐five articles regarding caries experience among type 1 diabetics were analyzed (Table ). Regarding type 2 diabetes 17 studies were included (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Orbak et al (28) reported higher incidence of decayed teeth in diabetic children at age 5-14 years old with poor metabolic control. Subramaniam et al (29) reported higher DMFT scores in diabetic children compared to healthy patients. On the other hand, some of the studies demonstrated lower number of decayed teeth (8,30), while the others reported similar number of decayed teeth in both diabetic and healthy individuals (9,31).…”
Section: Discussionmentioning
confidence: 99%